Promoting Italy through the radio in 1930: an analysis of ENIT radio broadcast in English (Altre Modernità, 2025)
The aim of this study is to investigate how Italy was promoted in English by means of the Radio-Giornale dell’ENIT in 1930. The materials retrieved from the Archivio Centrale dello Stato include 110 manuscripts of radio programmes in Italian and 5 manuscripts of radio programmes in English, all broadcast from July to December 1930. The study is focused on the radio programmes in English. The English scripts were annotated by means of QDA Miner Lite to identify the main content types drawing on existing classifications. Then, the pieces of news occurring both in the Italian and in the English scripts were compared to check whether literal translation from Italian into English took place or not, as well as to identify linguistic strategies adopted to cater for the needs of English-speaking travellers. In the conclusions, some observations regarding the promotion of Italy in English through the ENIT radio programmes will be provided.